Radiographic Native Femoral Head Size Correlates with Acetabular Cup Size in Primary Total Hip Arthroplasty - Pfeufer, Daniel; Gililland, Jeremy; Ajinkya, Rane; Duensing, Ian; Anderson, Mike B.; Peters, Christopher L.; Pelt, Christopher E. (The Journal of Hip Surgery, 2019)
There is very little literature on whether a simple radiographic measurement of native femoral head size correlates with implanted acetabular cup size. We hypothesized that there would be a high correlation between the radiographically measured native femoral head and implanted acetabular component size in primary total hip arthroplasty (THA). We conducted a retrospective study of 277 consecutive patients who underwent primary THA. Patients with prior contralateral THA or a history of congenital deformity were excluded (n = 95). We used the postoperative anteroposterior (AP) pelvic view to calibrate the image using known implanted femoral head component size. We then measured the diameter of the contralateral native femoral head under the assumption that femoral heads are generally symmetrical in patients. Two of the authors performed all measurements. To determine if native femoral head size was correlated with acetabular component size we used the Pearson correlation coefficient (r). There was a high correlation between contralateral native femoral head size and acetabular component size (r = 0.86, 95% confidence interval [CI]: 0.82–0.89). The median difference in radiographically measured native femoral head size and acetabular component size was 7 mm (interquartile range [IQR] = 5–8). Our data showed a high correlation between acetabular component size and radiographically measured contralateral native femoral head size, with the difference being 7 mm. In addition to verifying the actual femoral head size with calipers during surgery, this simple radiographic measurement, which could be done on the affected or contralateral hip, may help surgeons to plan better and improve preoperative templating in primary THA.
Keywords: primary total hip arthroplasty; preoperative planning and templating; acetabular component size